Pharmaceutical prescritions dispensed by compounding pharmacies in Cascavel - PR (Research, Society and Development, 2022)
The pharmaceutical prescription is one of the acts developed by the pharmacist, where he determines the appropriate pharmacotherapy for each patient to restore their health, i.e., it is a document that records the care, treatment and medication recommended by the pharmacist. The present study aimed to survey the number of pharmaceutical prescriptions received by compounding pharmacies in the city of Cascavel-PR, in order to verify the quantity and the most prescribed classes. The methodology applied is a descriptive documental research with a quantitative approach, where data collection was performed in two compounding pharmacies located in Cascavel-PR. The results were tabulated and 1.35% of prescriptions made by pharmacists were found in comparison with other prescribers. Were found 90.40% of prescriptions by physicians and 8.25% by nutritionists. It was found that the number of prescriptions made by pharmacists is still very low compared to physicians and nutritionists. Among the most prescribed classes of products, aesthetic products stand out (51.21%), compared to herbal medicines (37.42%) and products classified as supplements (11.37%). Thus, it is concluded that the presciptions by pharmacists is still low, but it is believed that over the years this number will increase significantly, because the pharmacist can prescribe and act in several areas and is seen as part of the multidisciplinary team and a key player in the promotion and restoration of health.